Ovarian development in swimming crabs: Comparative histochemistry and ultrastructure of Callinectes ornatus and Arenaeus cribrarius (Brachyura, Portunidae) - Garcia Bento, M. A. [UNESP]; Nascimento, F. A. [UNESP]; Mantelatto, F. L.; Zara, F. J. [UNESP] (Elsevier, 2020)
The ovarian development of Callinectes ornatus and Arenaeus cribrarius was described using histochemistry and ultrastructure. Both species shows the same ovarian stages, which are the juvenile (JUV), adult rudimentary (RUD), developing (DEV), intermediary (INT), mature (MAT), and spent (OV) stages. The JUV and RUD stages showed similar characteristics, and previtellogenesis is characterized by meiotic prophase chromosomes. In the primary vitellogenesis, the oocyte cytoplasm shows many small and large cytoplasmic glycoprotein vesicles. These vesicles correspond to the dilated cisternae of the rough endoplasmic reticulum (RER), which produces the immature (endogenous) yolk. Secondary vitellogenesis (exogenous phase) begins at the DEV stage with the fusion of pinocytic vesicles and vesicles with immature yolks to form mature yolk granules. At the INT stage, the formation of the chorion begins, and the mature yolks increase in size and number, while the RER diminishes. In the MAT stage, the oocytes are completely formed, and the cytoplasm is filled with mature yolk, lipid droplets, and glycogen. There are no significant variations between the gonadosomatic and hepatosomatic indices, which allows us to infer that the transfer of reserves from the hepatopancreas is nearly constant during ovarian development, since we observed primiparous and multiparous females in the same sampled population.
Keywords: GSI; Histology; HSI; Oocyte; Transmission electron microscopy